MASALAH HUTANG LUAR NEGERI INDONESIA DAN ALTERNATIF SOLUSINYA DALAM PERSPEKTIF KEBIJAKAN EKONOMI MAKRO ISLAM - muhaimin muhaimin (At-Taradhi Jurnal Studi Ekonomi, 2012)
This paper outlines Islamic macro economic policy on the issue of foreign debts andoffers solutions to resolve the crisis of foreign loans in a humane and socially just manner. Eco-nomic recovery can be done by the combination of reforming the morality of business actors andstate apparatuses, changing the economic structure to a more efficient one, emphasising a maxi-mum use of economic resources, and minimising the distribution gap in society by decentralisingwealth and completely removing injustice. Improvidence and consumptive tendencies of societyand state apparatuses must be pressed and accompanied by corruption elimination. Good gover-nance and peoples confidence are two high valued assets to run the development and to create ajust and properous society.